Translational design prototypes for interdisciplinary public transport research. (4th March 2022) - Fridman, Ilya
Abstract: This article contributes to the understanding of prototypes within translational design practice by analysing their application during interdisciplinary research. A case study is provided to showcase how prototypes facilitated interdisciplinary research progression on a public transport research project conducted through collaboration between four university faculties and an external industry partner. Two prototype dimensions are identified as being of significance for translational designers working within these contexts: collaboration and communication. The collaboration dimension represents the level to which prototypes invite input from non-design disciplines and external stakeholders in order to develop real-world applicable knowledge that can drive research translation. The communication dimension represents the level to which prototypes can communicate research outside of the project context and disseminate knowledge to broader audiences who can assist in advancing it towards implementation.